Differences in Pedagogical Competence of Shadows Teachers in Terms of Academic Qualification in Inclusive Elementary Schools in Surakarta City - Ramizah Ariq Sakinah Irvansyah; Herry Widyastono; Mahardika Supratiwi (Journal of Disability, 2023)
The purpose of this study was to determine the differences in shadow teachers’ pedagogical competence in terms of academic qualification. This research method used is comparative quantitative. The research involved two groups: the special education graduate group and the non-Special Education graduate group. The subjects of this study were 15 Shadow teachers with Special Education graduates and 23 Shadow Teachers with non-Special Education graduates spread across 19 elementary schools, including the city of Surakarta.Data collection techniques using the saturated sample method. The instrument used is a pedagogic competency scale with a reliability value of 0.905. In the shadow teacher group with Special Education graduates, 14 respondents were in the very high category, and 1 respondent was in the high category, with the highest score being 179 points and the lowest score being 136 points. Whereas in the shadow teacher group with non-Special Education graduates, 13 respondents were in the high category, and 10 respondents were in the high category, with the highest score of 170 points and the lowest score of 130 points. The analysis in this study used the Man Whitney-U test. The Mann-Whitney-U test shows the value Ucount = 0.220, which is UCount>U table (Utabel = 0.05). Research results conclude that there is no significant difference between the pedagogical competence of teachers with special education and non-special education graduates.